PTEN loss in biopsy tissue predicts poor clinical outcomes in prostate cancer. (5th August 2014) - Mithal, Prabhakar; Allott, Emma; Gerber, Leah; Reid, Julia; Welbourn, William; Tikishvili, Eliso; Park, Jimmy; Younus, Adib; Sangale, Zaina; Lanchbury, Jerry S; Stone, Steven; Freedland, Stephen J
<x xml:space="preserve">Abstract</x> Objectives To determine whether PTEN status in prostate biopsy represents a predictor of intermediate and long‐term oncological outcomes after radical prostatectomy, and whether PTEN status predicts response to androgen deprivation therapy. Methods In a retrospective analysis of 77 men treated by radical prostatectomy who underwent diagnostic biopsy between 1992–2006, biopsy samples were stained for PTEN expression by the PREZEON assay with >10% staining reported as positive. Cox proportional hazards and log–rank models were used to assess the correlation between PTEN loss and clinical outcomes. Results During a median follow‐up period after radical prostatectomy of 8.8 years, 39 men (51%) developed biochemical recurrence, four (5%) had castration‐resistant prostate cancer, two (3%) had metastasis and two (3%) died from prostate cancer. PTEN loss was not significantly associated with biochemical recurrence (hazard ratio 2.1, 95% confidence interval 0.9–5.1, P = 0.10), but significantly predicted increased risk of castration‐resistant prostate cancer, metastasis and prostate cancer‐specific mortality (all log–rank, P < 0.0001), and time from androgen deprivation therapy to castration‐resistant prostate cancer (log–rank, P = 0.003). No patient without PTEN loss developed metastases or died from prostate cancer. Conclusions PTEN loss at the time of biopsy seems to predict time to development of metastasis, prostate cancer‐specific mortality and, for the first time, castration‐resistant prostate cancer and response to androgen deprivation therapy after radical prostatectomy. If confirmed by larger studies, this would support the use of PTEN loss as an early marker of aggressive prostate cancer.